2012
DOI: 10.1093/europace/eur402
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammation in early atrial fibrillation recurrence

Abstract: In patients with short-lasting AF, early AF recurrence seemed to be associated with inflammation as represented by IL-6. Treatment aimed against inflammation may therefore prevent early AF recurrences, which can improve rhythm control outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 48 publications
0
54
0
Order By: Relevance
“…The strongest factor associated with long-term recurrence after ERAF was current tobacco use (HR, 3.84), which is postulated to facilitate arrhythmia recurrence through induction of inflammation, atrial fibrosis, or sympathetic neural stimulation. 17 Although we demonstrated an independent association between early reablation and improved long-term success, we cannot conclude that early reablation for ERAF after cryoablation is warranted in all. The nonrandomized decision to pursue reablation in the current study is subject to known Figure 2.…”
Section: Incidence Of Early and Late Recurrencementioning
confidence: 57%
“…The strongest factor associated with long-term recurrence after ERAF was current tobacco use (HR, 3.84), which is postulated to facilitate arrhythmia recurrence through induction of inflammation, atrial fibrosis, or sympathetic neural stimulation. 17 Although we demonstrated an independent association between early reablation and improved long-term success, we cannot conclude that early reablation for ERAF after cryoablation is warranted in all. The nonrandomized decision to pursue reablation in the current study is subject to known Figure 2.…”
Section: Incidence Of Early and Late Recurrencementioning
confidence: 57%
“…A recent study demonstrated that elevated levels of IL-6 were associated with early AF recurrence after electrical or chemical cardioversion [29]. In a cross-sectional analysis of 46 AF patients out of 971 participants in the Heart Soul Study, IL-6 was found to be the only biomarker significantly associated with AF [30].…”
Section: Discussionmentioning
confidence: 96%
“…It is noteworthy that one of these studies (negative for an association) had enrolled a cohort, 45% of which had diabetes, cardiac failure, and/or myocardial infarction as comorbidities, all known to be associated with inflammation (Kimmel et al, 2013), while the other two (one negative and one weakly positive for the association) included no information on comorbidities. Furthermore, and perhaps more crucially significant, there is a well-documented relationship between atrial fibrillation, the major indication for use of warfarin and other vitamin K antagonists in these studies, and raised inflammatory biomarkers, especially IL-6 (Henningsen et al, 2009;Marcus et al, 2010;Celebi et al, 2011;Smit et al, 2012;Wu et al, 2013). Inevitably, a question arises concerning the extent to which the CYP2C9 genotype of the cohorts of these three studies was predictive of their CYP2C9 phenotype.…”
Section: Discussionmentioning
confidence: 99%